(In)visíveis sequelas: a violência psicológica contra a mulher sob o enfoque gestáltico - FERREIRA, Wanderlea Nazaré Bandeira (Universidade Federal do Pará, 2014)
The psychological mode is best known for its "invisibility" in public because of, among other factors, occur more frequently in the private area, and also for not leave physical marks. Currently, Law 11340/2006, named as the "Maria da Penha Law" after sanctioned, translates one form of legal protection for women and institutionalized. Employ the concept of gender according to Scott (1991), as one of the analytical tools for identifying links between social and economic construction of violence and state policies. In this overview, we present the general objective of this research reveal some empirical (in) visible, psychological and social sequelae and specifically the impact on the subjectivity of women who experience situations of psychological violence occurring in the domestic sphere and within families. Analyses were performed in the Gestalt perspective, a psychological approach to conscious contact, which allows intervention to strengthen the internal support healthy and self-regulation in order to overcome situations that blur the roles and boundaries of contact. This is a clinical-qualitative research basic existential-phenomenological and hermeneutic-gestalt. The procedures used were project submission to the Ethics Committee of the CCS / UFPA; obtaining authorization Institutional; identify and invite three women to participate in the study, according to the profile of the sample: availability for the survey, aged 25 45 years, which has been or is experiencing psychological violence situation with her husband / partner. Afterwards, they signed the Deed of Consent and conducted semi-directed interviews with open questions (recorded on audio). They were transcribed and analyzed. The research site was the Reference Center Maria do Pará used for the analysis of the collected understanding Ricouer (1975) and the gestalt concept of contact, tasks and contact boundaries, defense mechanisms, self, awareness and creative adjustment . The result points to the unveiling of permeated experienced verbal abuse in the form of humiliation, curses, insults, jealousy, disqualification of his physical appearance, lack of dialogue, social and emotional isolation, fear, suffering, pain, grief, guilt, shame, feelings of hatred, anger, sadness and helplessness in the face of such violence. We conclude that the "invisibility" of such experiences of psychological violence generates visible breaks in touch with himself, his family relations and social, as well as prints deep and damaging deconstructed the personality and the way women express their subjectivity.